Aggregate Expected Consumer Surplus as a Welfare Index with an Application to Price Stabilization - Rogerson, William P. (Econometrica, 1980)
This paper presents necessary and sufficient conditions for the expected value of consumer surplus to correctly represent a consumer's preferences. A theorem characterizing utility functions which represent preferences over conditional probabilities is used to derive this. An application to price stabilization policy is presented.